In-silico screening and molecular docking study of selected flavonoids as a potential inhibitor against SARS-COV-2 3CLPRO - Nikka Feb A. Adlaon. 4 0 16; 5 (2022)
u
Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2022.
Keywords: 2 -- 0; 6; 20; 20; 2